Profile of the demand for microcomputers in Brazil: what do the POF-IBGE microdata indicate? (Revista de Administração, 2012)
This study investigated the relation between household spending on microcomputers and household socioeconomic and demographic characteristics. The authors used the microdata from two Household Budget Surveys (POF) conducted by the Brazilian Institute of Geography and Statistics (IBGE) in 2002-2003 and 2008-2009. This database made it possible to use the total spending per capita as the variable defining the purchasing power of households. The econometric approach adopted fits the nature of this type of analysis, i.e., the Heckman Selection Model, which involves two steps. First, the factors associated with the likelihood of spending were analyzed and then, the factors associated with spending. The main results show that the profile of the head of household (gender and age), household composition and education of the residents are relevant factors regarding two decisions: whether or not to spend and how much to spend. The reduction of the elasticity that relates the purchasing power of the household with spending on computers (in 2002-2003 it was 0.56763 but in 2008-2009 this figure fell to 0.41546) can be explained by the falling prices of computers and the rising purchasing power of the households.